A Specific and Covalent JNK‐1 Ligand Selected from an Encoded Self‐Assembling Chemical Library. Issue 34 (30th May 2017) - Zimmermann, Gunther; Rieder, Ulrike; Bajic, Davor; Vanetti, Sara; Chaikuad, Apirat; Knapp, Stefan; Scheuermann, Jörg; Mattarella, Martin; Neri, Dario
Abstract: We describe the construction of a DNA‐encoded chemical library comprising 148 135 members, generated through the self‐assembly of two sub‐libraries, containing 265 and 559 members, respectively. The library was designed to contain building blocks potentially capable of forming covalent interactions with target proteins. Selections performed with JNK1, a kinase containing a conserved cysteine residue close to the ATP binding site, revealed the preferential enrichment of a 2‐phenoxynicotinic acid moiety (building blockA82 ) and a 4‐(3, 4‐difluorophenyl)‐4‐oxobut‐2‐enoic acid moiety (building blockB272 ). When the two compounds were joined by a short PEG linker, the resulting bidentate binder (A82‐L‐B272 ) was able to covalently modify JNK1 in the presence of a large molar excess of glutathione (0.5 mm ), used to simulate intracellular reducing conditions. By contrast, derivatives of the individual building blocks were not able to covalently modify JNK1 in the same experimental conditions. TheA82‐L‐B272 ligand was selective over related kinases (BTK and GAK), which also contain targetable cysteine residues in the vicinity of the active site. Abstract : A novel covalent binder of JNK1, a kinase containing seven cysteine residues, including a conserved cysteine residue close to the ATP binding site, has been identified from a DNA encoded self‐assembling chemical library (ESAC). The binder showed the ability to covalently modify JNK1 in a 1:1 stoichiometry in the presence of a large molar excess of glutathione to mimic the intracellular reducing environment.